World without end [videorecording (DVD)] : the epic eight-part miniseries - Caton-Jones, Michael; Chaplin, Ben; Evans, Rupert; Riley, Charlotte; Follett, Ken
Set in England during the 1300s, the series chronicles the lives of ordinary citizens as the King leads the nation into the Hundred Years' War with France, all while Europe is bracing for the Black Death. Caris, a visionary woman, and her lover Merthin build a community that stands up to the Crown and the church.